Efficacy of Different Sequences of Radio‐ and Chemotherapy in Experimental Models of Human Melanoma. Issue 10 (October 2014) - Arienti, Chiara; Zoli, Wainer; Pignatta, Sara; Carloni, Silvia; Paganelli, Giulia; Ulivi, Paola; Romeo, Antonino; Menghi, Enrico; Sarnelli, Anna; Medri, Laura; Polico, Rolando; Silvestrini, Rosella; et al.
Abstract Although combination chemotherapy and radiotherapy have become the standard of care in numerous tumors, the mechanisms of interaction are often still unclear. The purpose of this study was to analyze the efficacy of radiation treatment and cisplatin sequences and to investigate their mechanisms of interaction. Three melanoma cell lines were used to evaluate in vitro radiation‐induced cytotoxicity before and after cisplatin treatment. Expression levels of a panel of genes were determined by real‐time RT‐PCR. Cytotoxic effect was evaluated by flow cytometry analysis and Comet assay. We also used normal human dermal fibroblasts (HUDE) to evaluate the cytotoxicity of the two treatments by clonogenic assay. Radiation and cisplatin used singly were not particularly effective in reducing proliferation in melanoma cells. Conversely, radiation treatment followed by cisplatin showed a strong synergistic interaction in all cell lines, with a ratio index ranging from 16 to >100. The synergistic effect was accompanied by apoptosis induction (up to 40%) and an increase in the percentage of comet‐shaped nucleoids from 85% to 99%. In parallel, our results also showed that radiation treatment of HUDE fibroblasts followed by cisplatin only induced weak cytotoxicity. Our findings highlight the efficacy of the sequence radiation → cisplatin in reducing cell proliferation and in inducing apoptosis in melanoma cell lines. This sequence also modulated a network of proteins involved in DNA damage repair. J. Cell. Physiol. 229: 1548–1556, 2014. © 2014 Wiley Periodicals, Inc.